LAYOUT DESIGN AND OPERATIONAL SYSTEM ANALYSIS OF MAKASSAR NEW PORT CONTAINER TERMINAL WITH A GREEN PORT CONCEPT - Agnus Dei Sunatoputra, Mario
Makassar New Port is one of the ports in Indonesia which is a gateway for national and international economic connectivity. Makassar New Port is located on Jalan Sultan Abdullah Raya, Kaluku Bodoa, Makassar City, South Sulawesi. Its development is carried out because the existing port in Makassar is inadequate to handle the incoming container flow. Besides, its development is carried out without applying the green port concept. In this final project about “Layout Design and Operational System Analysis of Makassar New Port Container Terminal with a Green Port Concept”, will be discussed regarding the layout design, operating system, and cost of the Makassar New Port Container Terminal. Besides, the design of the layout, operating system and costs of the Makassar New Port Container Terminal will also be discussed using the Green Port concept. The limitation of this thesis is not to discuss the layout design, operating system, and costs for each stage of development, but only for stage 3 of the Makassar New Port Container Terminal development. The results of this design are the jetty and stacking layout, capacity, financial analysis, and emissions analysis. The Makassar New Port Container Terminal design without using the green port concept produces 2,893,531 TEU berth capacity and 6,061,355 TEU stacking field capacity. While the design with the concept of green port produces 2,893,531 TEU berth capacity and 6,179,097 TEU stacking field capacity. After comparing capacity, financial analysis, and emissions analysis of the two designs, the chosen design is the Makassar New Port Container Terminal using the green port concept.